Producing legalists or dirty Harrys? Police education and field training - Fekjær, Silje Bringsrud (Policing and society, 2019)
This paper explores Nordic police students’ attitudes towards non-legalistic police work, based on a cross-national longitudinal survey (N = 1,438). We ask where police recruits in four different Nordic countries are placed along a legalistic-autonomous continuum, and how the exposure to field training affect their acceptance of Dirty Harry-inspired measures. We find quite large differences between student populations. The Swedish police students are the most sceptical towards non-legalistic measures, while the Danes are the most positive. Danish and Icelandic police students gradually come to accept less legalistic procedures while enrolled at the academy, while there are small changes among the Swedish and Norwegian students. Based on a difference-in-difference model, we conclude that being exposed to field training during education makes students more positive towards Dirty Harry-inspired measures, but the effect is small. Country-specific cultural traits, such as views of legality and law abidance, seem to be important.